Refractory Ascites: Treatment and Complications Utilizing Peritoneovenous (Denver) Shunt - Shadkam-Farrokhi, Parvaneh; Lee, Edward Wolfgang (Digestive Disease Interventions, 2017)
Intractable ascites has long been an antagonizing problem for patients and medical providers. It is debilitating and frequently cannot be prevented by standard medical therapy. Ascites is primarily managed with salt restrictions, diuretics, and repeated paracentesis for symptomatic relief. However, 10% of patients become refractory to this first line of treatment. Several surgical methods such as the insertion of peritoneovenous shunts and transjugular intrahepatic portosystemic shunts have become popularized treatment modalities for the control of refractory ascites. Nevertheless, controversy resides over what is the best treatment method for the improvement in patients' quality of life and survival rate. We herein explore the different medical and surgical methods available for the control of refractory ascites with a focus on the advantages and complications associated with the usage of Denver peritoneovenous shunts.
Keywords: Denver shunt; peritoneovenous shunt; TIPS; complications